Synthesis and immunogenicity of the linear conjugates of polyacrylic acid and antigenic peptide of human papillomavirus - Eguz, Ilke Sahin; Ihlamur, Murat; Abamor, Emrah Sefik; Topuzogullari, Murat (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Polyelectrolytes (polymers carrying positively or negatively charged groups) can be used as adjuvants in subunit vaccine formulations to increase the immunogenicity of antigenic molecules. A vaccine prototype can be obtained by covalently bonding antigenic molecules to polyelectrolytes or using their physical mixtures with polyelectrolytes. Covalent conjugates of polyelectrolytes with antigens are known to exhibit stronger immunogenicity compared to physical mixtures of antigens and polyelectrolytes. In this study, linear conjugates of polyacrylic acid (PAA) with an antigenic peptide sequence (STHVDIRTLEDLLMGW) of the HPV-16 E7 oncoprotein were produced. PAAs of different molecular weights with narrow dispersity were synthesized by RAFT polymerization. The linear conjugates of PAA and the peptide were obtained by covalent bonding via the chain-end thiol group of PAA and N-terminal maleimide group of the peptide using the maleimide-thiol reaction. For this purpose, the trithiocarbonate end group of the polymer was reduced with excess ethylenediamine to the thiol group. The produced PAA-peptide conjugates were characterized by GPC, fluorescence, and NMR spectroscopies. Conjugation efficiency was above 80% for all PAAs. Antigenic peptide conjugates of PAAs of different molecular weights were investigated in MTT and nitric oxide (NO) assays in which the linear PAA-peptide conjugates exhibit high biocompatibility and stimulated the macrophages to release high levels of NO.
Keywords: RAFT polymerization; Subunit vaccines; Polyacrylic acid; HPV; Polyelectrolyte-peptide conjugates; FUNCTIONAL POLYMERS; POLY(ACRYLIC ACID); IMMUNE-RESPONSES; NANOPARTICLES; COMPLEXES; ADJUVANTS; Polymer Science